The Influence of Hyperreality, Social Norms, Peer Pressure, and Advertising on the Rise of Underage Nicotine Consumption: A Case Study of South Kuta, Bali - Kirana Amelie Kuhn (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study investigates the impact of hyperreality, social norms, peer pressure, and advertising on underage nicotine consumption in South Kuta, Bali. The research aims to explore the factors influencing the normalization of smoking and vaping among adolescents and to provide actionable insights for public health interventions. A mixed-method approach was employed, utilizing quantitative surveys with 89 participants aged 12-18 and qualitative interviews with four participants aged 13-15. Data were analyzed using descriptive statistics and thematic coding to identify patterns and themes. Results reveal that 72% of respondents frequently encountered tobacco advertisements, predominantly on social media, which often portrayed nicotine use as glamorous and socially rewarding. Peer pressure was a significant factor, with 45% of participants acknowledging encouragement from peers to smoke or vape. Social norms further contributed to the perception of vaping as socially acceptable, with 69% of respondents noting its normalization in their circles. Despite vaping being seen as less harmful than traditional cigarettes, this belief was primarily shaped by advertising rather than evidence. The study concludes that hyperreality, combined with peer dynamics and cultural norms, significantly influences adolescent nicotine consumption. This highlights the need for stricter advertising regulations, media literacy education, and peer-focused interventions. The findings emphasize the importance of addressing these interconnected factors through comprehensive strategies to mitigate the rising trend of underage nicotine use in Indonesia.